Penerapan Pemberian Grasi Terhadap Terpidana Korupsi Oleh Presiden - Ave Agave Christina Situmorang; Wahyu Koncoro (Pusat Riset dan Inovasi Nasional, 2024)
Clemency is a pardon in the form of a change in commutation, reduction or elimination of a criminal offense for a convicted person given by the president based on the consideration of the Supreme Court. The granting of clemency by the president is a form of humanity and justice towards the citizens of the country. And every prisoner has the same right to apply for clemency to the president. Granting this clemency is a fulfillment of human rights and is the president's prerogative in granting forgiveness. However, there needs to be a classification of the crime to provide an opportunity to apply for clemency. Such as the crime of corruption which is an extraordinary crime. The criminal act of corruption is a crime that not only harms one person, but also harms the State and people of Indonesia. Of course, the aim of this research is to find out certain conditions for granting clemency to corruption convicts by the president. This research method uses normative juridical research methods. By referring to the law on clemency and criminal acts of corruption as well as the presidential decision to grant pardon to corruptors. The findings of this research are that it provides special considerations in submitting requests for clemency and evaluation so that the president and the Supreme Court can logically consider their decisions in looking at the convict's case.